Poly(lactic acid)-silkworm silk fibre/fibroin bio-composites: A review of their processing, properties, and nascent applications - O. S. Akintayo; J. L. Olajide; O. T. Betiku; A. J. Egoh; O. O. Adegbesan; O. O. Daramola; E. R. Sadiku; D. A. Desai (eXPRESS Polymer Letters, 2020)
The past few decades have witnessed an upsurge in the utilization of natural fibres in green materials advancement. This rise can be linked to calls from stakeholders, around the world, on the issue of sustainability and eco-friendliness. A shift from the utilization of non-biodegradable sources to renewable sources is a current area of intense research, which also stimulates industrial attention. Amongst the creations of nature, silkworm silk fibres have attracted considerable interest from materials science researchers. Inferable from its amazing biocompatibility, bioresorbability, and biodegradability, silkworm silk strands have been used in the improvement of polylactic acid/silk fibre biocomposites. Hence, with the continued use of these biocomposites in industrial and biomedical applications, it has become necessary to look at the systematic progress made in its processing, overall property improvements, and various applications. This review article also presents the challenges facing the advancement of this biocomposite, the suggested solutions and concludes with anticipated future trends.